The potential for traditional Chinese therapy in treating sleep disorders caused by COVID-19 through the cholinergic anti-inflammatory pathway - Xie, Xiaoxia; Zhang, Nana; Fu, Jingya; Wang, Zhenzhi; Ye, Zirun; Liu, Zhijun (Frontiers in Pharmacology, 2022)
Since the outbreak of Coronavirus disease (COVID-19) in 2019, it has spread rapidly across the globe. Sleep disorders caused by COVID-19 have become a major concern for COVID-19 patients and recovered patients. So far, there’s no effective therapy on this. Traditional Chinese medicine treatment has a great effect on sleep disorders, with rare side effects and no obvious withdrawal symptoms. The cholinergic anti-inflammatory pathway, a neuroregulatory pathway in the central nervous system that uses cholinergic neurons and neurotransmitters to suppress inflammatory responses, has been reported to be associated with sleep disorders and psychiatric symptoms. Many studies have shown that TCT activates CAP, inhibits inflammation, and relieves associated symptoms. Therefore, we believe that TCT may be a potential therapeutic strategy to alleviate sleep disorders induced by COVID-19 through CAP. In this review, we analyzed the relationship between cytokine storm induced by Coronavirus and sleep disorders, explained the influence of CAP on sleep disorders, discussed the TCT's effect on CAP, and summarized the treatment effect of TCT on sleep disorders. Based on these practical researches and theoretical basis, we propose potential strategies to effectively improve the sleep disorders caused by COVID-19.